Feasibility study of investment projects - Budimir Branka (Trendovi u Poslovanju)
Prior to execution of the project of any kind, it is necessary to consider all factors relevant to the realization of the project. All the activities of collection and analysis of information related to the assessment of the validity of a project make a feasibility study altogether. The feasibility study is a complex investment elaborate detailing and comprehensively examining the possibility of realization of a particular investment project, as well as justification i.e. the rationality of the investment.